THE RELATIONSHIP BETWEEN PARENTING PATTERNS AND GADGET ADDICTION LEVELS IN PRESCHOOL CHILDREN IN RT. 003/ RW. 005 EAST BEKASI DISTRICT BEKASI CITY - Adhitamy Shimanovsky, Febby; Lisna Agustina; I Ratnah (Jurnal Medicare, 2023)
In the world, 72% of children under the age of six years have started using smartphones since 2013, where the majority of children aged 3 years prefer to use smartphones every day. This figure has doubled compared to 2011 which was still at 38%. Parenting patterns are things that affect the level of gadget addiction in preschool children. The reasons parents give gadgets to children when parents are doing homework are 70%, to keep children calm 65%, and time before going to bed 25% (Kabali et al, 2015). According to Sunita (2018), saying that children become happy playing gadgets because of various interesting things in it, it makes children want to always use gadgets. This can slowly change children's behavior so that they are not aware that excessive use of gadgets can cause children to become addicted to gadgets (Kwon, 2013). To determine the relationship between parenting style and the level of gadget addiction in preschool children in the RT. 003/ RW. 005 East Bekasi District, Bekasi City. The research method used a cross sectional design. The sampling technique was total sampling, with a total sample of 64 respondents. The instrument used is a questionnaire. Based on data analysis used by using Chi Square Test with p = 0.001 (p < 0.05). The conclusion is that there is a relationship between parenting patterns and the level of gadget addiction in preschool children in the RT. 003/ RW. 005 East Bekasi District, Bekasi City.